2015
DOI: 10.1016/j.jaci.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the epithelial anion transporter pendrin/SLC26A4 in nasal polyps of patients with chronic rhinosinusitis

Abstract: Background Chronic rhinosinusitis (CRS) is a multifactorial disease of unknown etiology characterized by sinonasal inflammation, increased mucus production and defective mucociliary clearance. Pendrin, an epithelial anion transporter, is increased in asthma and chronic obstructive pulmonary disease. Pendrin increases mucus production and regulates mucociliary clearance. Objectives We sought to investigate the expression of pendrin and the mucus-related protein Muc5AC in sinonasal tissues of control and CRS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 40 publications
2
68
0
2
Order By: Relevance
“…Similar results were found in HBE and CFBE cultures. Quantitative PCR analysis indicated that pendrin transcript levels were increased by 30-to 35-fold in the HBE and CFBE cultures (data not shown), similar to fold increases previously reported in similar cell systems (24,25,35).…”
Section: Specificity Of Pds Inh -A01 In Human Airway Epithelial Cell supporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were found in HBE and CFBE cultures. Quantitative PCR analysis indicated that pendrin transcript levels were increased by 30-to 35-fold in the HBE and CFBE cultures (data not shown), similar to fold increases previously reported in similar cell systems (24,25,35).…”
Section: Specificity Of Pds Inh -A01 In Human Airway Epithelial Cell supporting
confidence: 87%
“…More recently, Button and colleagues (52) showed that tethered mucins in the PCL form a mesh to prevent entry of gel-forming mucins and support ciliary beating, and they proposed a gel-onbrush model to describe the ASL. Photobleaching studies support this concept and have established that the fluid phase viscosity of the mucus layer and PCL are similar in non-CF subjects (7-10 times more viscous than saline), but significantly elevated in both regions in CF cultures (25)(26)(27)(28)(29)(30) times more viscous than saline) (51). In addition to forming a permeability barrier, tethered mucins in the PCL generate an osmotic pressure to regulate PCL hydration (52).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…For example, levels of epithelial-derived antimicrobial proteins including lysozyme, S100A7, S100A8/9, beta-defensins, and Palate, Lung, and Nasal Epithelial Clone (PLUNC) proteins were reduced in CRSwNP patients compared to healthy controls 272830 . Pendrin, an epithelial ion transporter that can increase mucus production, and Muc5AC, a type of mucin, were elevated in CRSwNP versus controls 3132 . These findings suggest that impairment in mucociliary clearance, reduction in antimicrobial defense protein secretion, and breakdown in the physical barrier can lead to chronic exposure of pathogenic and non-pathogenic mediators and the development of a chronic inflammatory response.…”
Section: Pathophysiologymentioning
confidence: 95%
“…The reciprocal regulatory interaction between the SLC26 and CFTR involves binding of the STAS domain to the regulatory domain of CFTR (see section on pancreas). The SLC26 transporter SLC26A4, pendrin, has been shown to be upregulated in inflammatory conditions in airway epithelia such as chronic rhinosinusitis [92, 93], upon stimulation with IL-17 [94] and in response to bacterial infections [95]. The other mechanism that involves CFTR in ASL pH regulation is its capacity to regulate Cl − /HCO 3 − anion exchange, and more particularly, SLC26A4 in airway epithelial cells.…”
Section: Role Of Cftr In the Lungsmentioning
confidence: 99%